2004
DOI: 10.1111/j.1469-0691.2004.00919.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a cefoxitin disk diffusion test for the routine detection of methicillin-resistant Staphylococcus aureus

Abstract: Two oxacillin disk methods were compared with a cefoxitin disk diffusion test for detection of methicillin-resistant Staphylococcus aureus (MRSA), with PCR for mecA as the reference method. When tested with 115 MRSA and 350 methicillin-susceptible S. aureus isolates, the cefoxitin disk test (specificity 100%, sensitivity 96.5%) was superior to the oxacillin disk methods (specificity 99.1%, sensitivity 90.4%). Testing with both oxacillin and cefoxitin disks would give better sensitivity (100%) than the cefoxiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
36
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 19 publications
9
36
0
2
Order By: Relevance
“…These results are in accordance with previously reported studies [16] [17]. Although some publications revealed the higher sensitivity for disk diffusion test with cefoxitin (95% -100%), in our research the sensitivity for DDT with cefoxitin was considerably lower (83.33% (95% CI 62.6% -95.16%)).…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with previously reported studies [16] [17]. Although some publications revealed the higher sensitivity for disk diffusion test with cefoxitin (95% -100%), in our research the sensitivity for DDT with cefoxitin was considerably lower (83.33% (95% CI 62.6% -95.16%)).…”
Section: Discussionsupporting
confidence: 93%
“…Use of the oxacillin DD test for the detection of MR staphylococci was less specific compared with the cefoxitin DD test, as also reported by Palazzo & Darini (2006). It has been reported that oxacillin resistance among staphylococci is caused by expression of PBP2a encoded by the mecA gene, which has a low binding affinity to all b-lactam antibiotics available in clinical practice (Boutiba-Ben Boubaker et al, 2004b;Cauwelier et al, 2004;Skov et al, 2003). Detection of oxacillin resistance is complicated because different populations of staphylococci express different levels of resistance.…”
Section: Strainmentioning
confidence: 84%
“…Specificity for the cefoxitin disc was 100 %, whereas that for the oxacillin disc was 99.2 %. Various workers have shown that the cefoxitin disc method has better sensitivity than the oxacillin disc method for MRSA detection (Velasco et al, 2005;Boutiba-Ben Boubaker et al, 2004;Skov et al, 2003). This higher sensitivity to cefoxitin can be explained by the increased expression of the mecA-encoded protein PBP2a, cefoxitin being an inducer of the mecA gene (Velasco et al, 2005).…”
Section: Discussionmentioning
confidence: 99%